Is money buying better results at PISA and INVALSI tests? The Italian case - Savino, Gaetano (2019)
“More effort of the South is needed. You need to work hard. This is needed.” So spoke the Italian Minister of Education in the province of Naples. He did so when asked whether Southern Italy would receive more funds to fill its long-standing and wide gap against the Centre-North at the national and international large-scale assessments on learning. The difference between the two macro-regions is remarkable, and it amounts to more than one year of schooling according to several studies. Every day-after the publication of the results of the international PISA or the national INVALSI, they repeat the pattern shown in previous edition and revive the long debate about Southern efficiency. Indeed, several research papers found that actually the South receives more than the Centre-North for education, though, results are not converging. This text shows that the difference between the scores of the two Italian macro-regions is statistically significant and acknowledges the lack of convergence. Further, it inserts Mezzogiorno and Centre-North values in four different frameworks that study the relationship between expenditure on education and GDP per capita with PISA scores. Results suggest that Mezzogiorno is already in a situation where more funds are not associated with better results. This gap is only one of a long list that see Mezzogiorno lagging behind the Centre-North, in Italy, the land of variances. Filling the education gap would be the first step to revamp the Southern human capital, where talent, from decades has been migrating towards the Centre-North.